2005
DOI: 10.1111/j.1550-7408.2005.3291rr.x
|View full text |Cite
|
Sign up to set email alerts
|

Complete Sequence and Gene Organization of the Nosema spodopterae rRNA Gene

Abstract: By sequencing the entire ribosomal RNA (rRNA) gene of Nosema spodopterae, we show here that its gene organization follows a pattern similar to the Nosema type species, Nosema bombycis, i.e. 5'-large subunit rRNA (2,497 bp)-internal transcribed spacer (185 bp)-small subunit rRNA (1,232 bp)-intergenic spacer (277 bp)-5S rRNA (114 bp)-3'. Gene sequences and the secondary structures of large subunit rRNA, small subunit rRNA, and 5S rRNA are compared with the known corresponding sequences and structures of closely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 17 publications
(34 reference statements)
5
37
0
1
Order By: Relevance
“…Therefore, other markers were required for analyzing phylogenetic affinities. Tsai et al (2005) suggested that the microsporidian ITS and LSU rRNA sequences have good potential as informative molecular markers. According to the results of this study, the identity of the rRNA gene sequences of Vairimorpha sp.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, other markers were required for analyzing phylogenetic affinities. Tsai et al (2005) suggested that the microsporidian ITS and LSU rRNA sequences have good potential as informative molecular markers. According to the results of this study, the identity of the rRNA gene sequences of Vairimorpha sp.…”
Section: Discussionmentioning
confidence: 99%
“…The reverse organization of rRNA of Nosema was suggested as distinct characteristics of the 'true' Nosema group (Tsai et al, 2005;Kyei-Poku et aI., 2008). Our phylogenetic analysis seems to support this idea, since all known Nosema species with rRNA reverse arrangement fall in the group.…”
Section: Discussionmentioning
confidence: 99%
“…cPP, Nosema sp. co and Nosema disstriae (Huang et al 2004, tsai et al 2005, Wang et al 2006, Ku et al 2007, Kyei-Poku et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Tsai et al (2005) suggested that the reversed arrangement of rrNA genes such as lsU-ssU-5s arrangement may be a specific characteristic suitable for identification of Nosema species (Huang et al 2004(Huang et al , tsai et al 2005(Huang et al , ironside 2007. However, there are a few exceptions: refardt and Mouton (2007) and Xu et al (2011) reported a similar reverse rrNA arrangement of rrNA subunits in Glugoides intestinalis and Endoreticulatus sp., respectively.…”
Section: Discussionmentioning
confidence: 99%